Les obligations internationales de l’Etat d’accueil d’un investissement étranger et leur sanction dans l’ordre juridique international - Edouard, Régis (Université Paris 10, 2017)
L’encadrement, par le droit international, du comportement de l’État hôte d’un investissement étranger n’est concevable que dans la mesure où sa souveraineté est limitée, l’enjeu étant la sanction de l’inobservation, par cet État, de ses obligations. Ces dernières sont issues de la pratique conventionnelle, surtout bilatérale, regroupant des traités qui disposent au fond. L’«internationalisation» du régime juridique de l’investissement n’est pas exclue comme mode de formation d’obligations mais ne se produit qu’à la faveur de dispositions dotées d’un tel effet. La pratique conventionnelle, assez uniforme, a comme principale caractéristique l’articulation de règles limitant le besoin d’interprétation autour de standards qui l’amplifient. Ceci, de même que les interprétations arbitrales, autorise à soupçonner une volonté de « remembrement » du standard minimum international. Si l’attribution d’un comportement à l’État d’accueil ne pose pas de difficulté inédite, l’établissement d’une violation, par cet État, de « ce qui est requis de lui » révèle des singularités de ce domaine. La qualification des circonstances excluant l’illicéité en situation d’urgence peut s’avérer problématique, le risque étant omniprésent d’une méconnaissance, de la part des arbitres, de la logique du droit de la responsabilité. En dehors de ces situations, on peut imaginer des hypothèses dans lesquelles l’illicéité est exclue suite au consentement de l’État d’origine ou de l’investisseur. Le préjudice subi par ce dernier, objet de la réparation intégrale due par l’État responsable, constitue le « préjudice causé par le fait internationalement illicite ». Il est immédiat et direct. L’investisseur, titulaire du droit d’invocation de la responsabilité de l’État hôte, a accès à une réclamation internationale qui éclipse celle de son État de nationalité. La perspective d’un endossement, par ce dernier, de la réclamation de son national accroît l’efficacité des traités d’investissement. For the conduct of a foreign investment’s host State to be governed by international law is only conceivable insofar as its sovereignty is limited, since the issue is the sanction of the failure of that State to fulfill its obligations. The latter results from a mostly bilateral treaty practice embodying treaties which contain material provisions. The “internationalization” of the legal regime of an investment is not excluded as a means to create obligations, but only occurs through provisions with such an effect. The main characteristic to this fairly uniform treaty practice is the development of rules limiting the need for interpretation around a core set of standards amplifying it. This, as well as the arbitral interpretations, may reflect a desire to “consolidate” the international minimum standard. If the attribution of conduct to the host State does not raise any unprecedented issue, the establishment of a violation by that State of “what is required of it” reveals singularities in this field. The characterization of circumstances precluding wrongfulness in an emergency situation may prove problematic, as the risk that arbitrators may ignore the logic of the law of responsibility is omnipresent. Apart from these situations, it is possible to imagine hypotheses in which wrongfulness is precluded due to the consent of the State of origin or the investor. The injury sustained by the latter, which is the subject of full reparation due by the responsible State, constitutes “injury caused by the internationally wrongful act.” It is immediate and direct. The investor, entitled to invoke the responsibility of the host State, has access to an international claim which eclipses that of his State of nationality. The prospect of an espousal by the latter of its national’s claim increases the effectiveness of the investment treaties.
Keywords: Arbitrage transnational; Foreign investment; International responsibility; Investissement étranger; Investissements étrangers (droit international); Investment treaty; Investments; Obligation primaire; Obligations internationales; Primary obligation; Responsabilité internationale; Souveraineté; Sovereignty; Traité d’investissement; Transnational arbitration; État (responsabilité)

Recherche sur la notion d'investisseur protégé par le droit international - Atanasov, Ognyan (Université Paris 1, 2017)
A la différence d'autres catégories de personnes privées, comme par exemple celle des commerçants qui, s'ils peuvent tirer profit des règles internationales mises en place par les États relatives au libre exercice du commerce, n'ont généralement pas la capacité de se prévaloir à titre individuel des droits leur conférant ces règles dans l'ordre international, l'investisseur est devenu aujourd'hui destinataire direct d'un nombre important d'instruments conventionnels, et dispose grâce aux mécanismes de règlement des différends prévus par ces derniers d'un droit d'action individuel à l'encontre des États étrangers. Par le terme « investisseur», les conventions de protection des investissements étrangers désignent aussi bien les individus que les personnes morales. Traditionnellement, en contentieux interétatique, un État ne peut exercer sa protection diplomatique qu'en faveur de ses nationaux, à condition cependant que l'individu ne possède pas en outre la nationalité de l’État destinataire d'une telle réclamation. Le droit conventionnel des investissements a apporté une certaine évolution en la matière. D'une part, de plus en plus de traités étendent leur application non seulement aux nationaux des États contractants, mais également aux individus ayant établi leur résidence sur le territoire de ces derniers. D'autre part, certaines conventions prévoient expressément que lorsqu'un individu-investisseur dispose à la fois de la nationalité de l'un des États contractants d'un traité et de celle d'un autre État contractant, contre lequel il entend adresser une réclamation, c'est la nationalité la plus effective de la personne physique qui doit conditionner la recevabilité de sa demande au niveau international. Concernant le régime de protection des personnes morales, en contentieux de la protection diplomatique la Cour internationale de Justice accorde uniquement à l’État où est constituée la société, le titre pour agir en sa faveur à l'encontre d'un autre État. Cette règle a été très critiquée au motif que souvent l’État d'incorporation d'une société, contrôlée par des ressortissants d'un autre État, n'a pas toujours un intérêt suffisant pour défendre les droits de celle-ci vis-à-vis d'un troisième État auteur d'une mesure préjudiciable pour cette société. L’État réellement intéressé par un recours serait plutôt celui de nationalité des associés de la personne morale lésée. En tenant compte de ce dernier constat, le droit conventionnel des investissements a conféré la capacité aux associés d'une société lésée pour agir en protection des actifs de cette dernière, sans pour autant remettre en cause la qualité à agir de la société pour la protection de ces mêmes biens et avoirs. Lorsque le titulaire d'un investissement est une personne morale, celle-ci n'est alors plus perçue comme un seul investisseur, mais comme une pluralité d'investisseurs potentiels. La société peut être traitée soit comme une personne juridique unique, soit comme une addition des personnalités de tous ses associés, détenant directement ou indirectement son capital, et disposant le cas échéant de nationalités différentes, et donc de titres juridiques multiples leur permettant d'agir à l'encontre de l’État ayant porté atteinte à l'investissement réalisé par une telle personne morale.
Keywords: Clause de déni des bénéfices; Corporate law; Droit des sociétés; Droits des associés; International law; Intérêt social; Investissements étrangers (droit international); Investisseur; Investments; Investors; Nationality; Nationalité; Rights of the associates; Résidence; Société

Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

Le règlement par voie d'arbitrage des litiges relatif aux investissements dans l'espace OHADA - Kenfack Douajni, Gaston (Revue juridique de l'Océan Indien, 2017)
Keywords: Arbitrage; Arbitragem; Arbitration; Clause compromissoire; Commission des Nations Unies pour le droit commercial international (CNUDCI); Contrat; Convention d'arbitrage; Exequatur; Investissements; Investments; Jurisprudence arbitrale; Loi nationale; Organisation pour l'harmonisation en Afrique du droit des affaires (OHADA); Règlement des litiges; Sentence arbitrale; Traité de protection des investissements

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

Foreign Direct Investment and Economic Development in Africa - Adegboye, F. B.; Ojo, Joshua A. T.; Olokoyo, F. O. (Journal of Internet Banking and Commerce, 2017)
Africa unlike other developing regions of the world has experienced declining flows of foreign direct investment (FDI).The flow of FDI is expected to result into gradual reduction in reliance on external borrowed capital and acceleration of economic development. The study examined the declining flow of FDI to the African regions as well as the impact that it has had on economic development of the region, using the proxies of Income per capita, Life expectancy and Education indices. The study made use of pooled data from thirty nine African countries within the period 1993 and 2012.The method of analysis utilized for the study was the fixed effect least-square dummy variable model, employed to estimate the impact of foreign direct investment on economic development for the selected host African countries. The study finds that foreign direct investment is statistically significant in relation to economic development for host African countries. It is therefore recommended that the governments of host countries should consider closely the sectors that FDI flows into, encourage investment domestically in such sectors such that dependence on external financial flows could be reduced, resulting in sustained increases in income, literacy level and hence improved life expectancy which are expected to result into sustained economic development.
Keywords: Economic Development; Foreign direct investment; Host African Countries; Income Per Capital; Investments; Life Expectancy

Comportement des entreprises en matière d’investissements immatériels : état des lieux et déterminants en contexte camerounais - Gonne, Jérôme; Feudjo, Jules Roger (La Revue Gestion et Organisation, 2017)
Résumé Les facteurs de compétitivité des entreprises dans la nouvelle économie ont changé de nature, passant des éléments physiques aux éléments immatériels. L’objectif de cette communication est donc d’analyser les spécificités des entreprises au Cameroun en matière d’investissements immatériels. Les données de l’étude ont été collectées auprès d’un échantillon de 78 entreprises opérant dans divers secteurs d’activité au Cameroun. Les résultats obtenus soulignent que les investissements immatériels font désormais partie intégrante des habitudes des entreprises camerounaises. Quelques actifs issus de ces investissements y trouvent un marché florissant. Cependant, on peut déplorer dans la majorité de ces entreprises un faible niveau d’investissements immatériels et une déficience de la qualité de l’information comptable et financière relative à ce type d’investissements. Nous relevons par ailleurs que, contrairement à l’intensité immatérielle, la qualité de l’information sur les immatériels semble dépendre de certains facteurs caractéristiques de l’entreprise. The factors of competitiveness of companies in the new economy have changed in nature from physical elements to intangible elements. The purpose of this communication is therefore to analyze the specificities of companies in Cameroon relating to intangible investments. The study's data was collected from a sample of 78 companies operating in various industries in Cameroon. The results emphasize that intangible investments are now part of the habits of Cameroonian companies. Some assets from these investments find in Cameroonian context a flourishing market. However, it is regrettable that the majority of these companies have a low level of intangible investment and impairment of quality of accounting and financial information for this type of investment. We further note that, contrary to the intangible intensity, the quality of information on intangibles seems to depend on some characteristic factors of the company.
Keywords: Accounting information; Cameroon; Cameroun; Companies; Entreprises; Information comptable; Intangible investments; Investissements; Investissements immatériels

Intégration régionale et investissements directs étrangers en Afrique - Mama, Hamimida (Revue Interventions économiques, 2017)
Le continent africain, un grand importateur de denrées alimentaires, connait des épisodes de crises alimentaires. En même temps et paradoxalement, les accords étrangers de leasing de terres sont en hausse depuis 2001. Les avantages que les investissements directs étrangers (IDE) procurent ne sont pas automatiques et ne profitent pas de manière égale aux pays d’origine et aux pays d’accueil. Souvent pour ces derniers, quand il s’agit de pays en développement ou des pays les moins avancés, la c...

Investissements d’accord, mais financement d’abord - Zogning Nguimeya, Felix (Revue Interventions économiques, 2017)
Les banques en Afrique subsaharienne ne possèdent toujours pas de système d’informations leur permettant d’accéder au dossier de crédit des opérateurs économiques qui sollicitent un financement. Si les experts, observateurs et investisseurs s’accordent sur le fait que l’heure est résolument à l’Afrique, que son immense potentiel augure des investissements prometteurs, il reste que le continent n’a toujours pas trouvé le véhicule de financement idéal pour soutenir, voire accélérer sa croissanc...

Financial Development, Integration and Access to Finance in Africa - Essien, Grace Etim (University of Leeds, 2017)
This thesis is made up of three empirical studies that fall under the general classification of international and financial economics, particularly the study focuses on the financial system of selected African countries. The first empirical study presented in Chapter 2 examines the role of financial development in improving the effect of FDI on the economic growth of some African countries. Investigations were conducted to pinpoint which financial structure could provide the best improvement by applying the bank-based vs. market-based debate. Results from the regression analysis conducted show that the effect of FDI on economic growth becomes significant only when financial development measures were factored in. Analysis of results indicate that development of the overall financial system of African countries would be more beneficial in comparison to developing either the banks or financial markets alone. Chapter 3 empirically measures the level of financial integration in Africa’s Regional Economic Communities (RECs) using beta and sigma convergence to measure the speed and degree of financial integration in four RECs. These chapter also theoretically examines how regional financial integration contributes to financial development and economic growth in Africa. Analysis of the results show that Africa’s RECs are integrating at a relatively slow and diverse rate. Therefore, policy makers in Africa would need to focus on reform strategies that would strengthen financial integration in their regions. A fully financially integrated system would contribute immensely to financial development and promote sustainable economic growth. The fourth chapter investigates the effect of access to finance on firms’ productivity. Using cross-sectional firm-level data to estimate the effect of access to finance on labor productivity, total factor productivity (TFP), and the stochastic frontier trans-log model. This study estimates an instrumental variable (GMM) model to address potential endogeneity bias between access to credit and firms’ productivity. The results obtained show that the lack of access to finance negatively affects the productivity of firms in Africa. This study suggests that the development of a balanced financial system should be of topmost priority to policy makers. This ensures that more finance is channelled towards those firms whose productivity depends heavily on the availability of finance irrespective of their characteristics. This would result in firms increasing their investments in productivity-enhancing activities, which would benefit long-term economic growth

China's legal obligations in the field of foreign investment : how trade agreements influence the formation of investment agreements? - Hua, Yuting (European University Institute, 2017)
Since deeper 'open-door' domestic reform in 1992, China has consistently maintained its position as the largest foreign direct investment (FDI) recipient among developing countries. In recent years China is going global as well. Accompanied with a large amount of outbound FDI, the level of debt is also increasing. Thus it is necessary for China to adopt a sustainable development policy and behave based on rules. China needs to work with the world to promote a rules-based investment climate. At a multilateral level, China joined the World Trade Organization (WTO) in 2001 and promised general and specific obligations on market entry and non-discrimination principles. Bilaterally, only after 2001, China has started negotiating preferential trade agreements (PTAs). The first part of the thesis analyses China’s legal obligations in investment agreements in pre- and post-WTO entry phases. Chapter 1 introduces China’s investment policy before 2001. Chapter 2 clarifies China’s commitments on non-discrimination principles under the WTO agreements, especially China’s Protocol of Accession. Chapter 3 compares Chinese BITs and PTAs with regard to investment principles. The second part of the thesis concerns interpretation on substantive and procedural provisions. Chapter 4 tries to answer the question of whether and how do tribunals consider jurisprudential concepts developed in the case law of the trade regime when resolving investment cases. Chapter 5 examines different remedies in trade and investment agreements. It is important for China to keep compliance with its commitments in international agreements, otherwise, it would face countermeasures which are highly costly. Also, China can implement competition rules in its domestic market for improving firms’ efficiency. Meanwhile, a balancing approach which emphasizes corporate social responsibility is equally important for China’s companies going global.
Keywords: Foreign investment; Foreign trade regulation; WTO; World Trade Organization

L'Etat dans l'arbitrage d'investissement - Ranjeva, Hery Frédéric (Revue juridique de l'Océan Indien, 2017)

The responsibility of private actors in the internal market : private actors taking over? - Trommer, Jan (European University Institute, 2017)
The picture presented and often referred to in EU internal market law and legal scholarship is clear. Within the internal market private actors are the recipients of rights and public authorities are constrained in their (regulatory) powers. The notion of this new individualism is bound up with capacities, powers, and resources that empower private actors to engage in the internal market and cross-border situations; ultimately serving the objectives the internal market seeks to attain. Yet, within thinew individualism a conceptually different class of private actors has emerged that is constrained in economic freedoms, i.e. through obligations, rather than being empowered in the context of the internal market. This thesis will enquire the reasons that led to the development of this counter-culture. Why did it emerge? To what extent does this phenomenon affect the roles of private actors in the internal market? I will demonstrate that under the counter-culture private actors are responsibilized and transformed into ‘competent authorities’, i.e. alternative forms of regulatory authority, in the internal market. Private actors are placed into systems of shared responsibilities the relationships of which are coordinated by EU internal market law. In this regard, the concept of responsibility will serve as a tool to bridge the gap between the new positions EU internal market law allocates to private actors and the emerging legal consequences, i.e. allocation of obligations or tasks. The legal contexts of EU free movement law, EU discrimination law, EU food safety law and EU data protection law will serve as case studies against which the construed conceptual framework will be tested. Under the counter-culture the new individualism is no longer only about the exercise of self-interests. Rather, this form of the new individualism comes with a requirement to give account to the interests of other actors within the internal market.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation